Cation Specificity of Vacuolar NHX-Type Cation/H+ Antiporters. Issue 2 (29th November 2018) - Bassil, Elias; Zhang, Shiqi; Gong, Haijun; Tajima, Hiromi; Blumwald, Eduardo
Abstract : NHX-type vacuolar cation/H + antiporters control vacuolar pH and K + and Na + transport. Abstract: Cation/H + (NHX-type) antiporters are important regulators of intracellular ion homeostasis and are critical for cell expansion and plant stress acclimation. In Arabidopsis ( Arabidopsis thaliana ), four distinct NHX isoforms, named AtNHX1 to AtNHX4, locate to the tonoplast. To determine the concerted roles of all tonoplast NHXs on vacuolar ion and pH homeostasis, we examined multiple knockout mutants lacking all but one of the four vacuolar isoforms and quadruple knockout plants lacking any vacuolar NHX activity. The nhx triple and quadruple knockouts displayed reduced growth phenotypes. Exposure to sodium chloride improved growth while potassium chloride was deleterious to some knockouts. Kinetic analysis of K + and Na + transport indicated that AtNHX1 and AtNHX2 are the main contributors to both vacuolar pH and K + and Na + uptake, while AtNHX3 and AtNHX4 differ in Na + /K + selectivity. The lack of any vacuolar NHX activity resulted in no K + uptake, highly acidic vacuoles, and reduced but not abolished vacuolar Na + uptake. Additional K + /H + and Na + /H + exchange activity assays in the quadruple knockout indicated Na + uptake that was not H + coupled, suggesting the existence of an alternative, cation/H + -independent, Na + conductive pathway in vacuoles. These results highlight the importance of NHX-type cation/H + antiporters in the maintenance of cellular cation homeostasis and in growth and development.